Effectiveness of Curricula in Creative Thinking of University Students: A Comparative Longitudinal Study - Naser, Ibrahim Muhi (International Journal of Psychosocial Rehabilitation, 2020)
Colleges in Iraqi universities are depending on different curricula and courses in preparing their students and cadres. These courses differ from one college to another according to the specialization or department sometimes. However, all students are joining these colleges from the secondary education stage, as they study at that stage with a unified curriculum in terms of goals and content, after their completing the secondary stage, they undergo with a comprehensive competitive test, accordingly, they are classified and accepted into the colleges of Iraqi universities, when they join to these universities, they undergo different educational curricula in terms of goals, content and method of teaching. Here, the students begin for receiving different courses that affect their knowledge structure with a different effect. Therefore, the researcher worked on conducting a study to know the effectiveness of these curricula in college students through conducting a longitudinal study that extended for four years, during which different groups of students were followed in different colleges, where at the beginning of their joining in the college, their level of creative thinking was measured with a scale which has been for this purpose, their scores were obtained in the general test for the secondary stage while their equivalence with these variables was confirmed by analysis of variance, it was found that, there were no statistically significant differences, after following them for four years during their university studies, also after their graduation, they were undergo again to the scale of creative thinking, as here the researcher has obtained the results that were statistically processed by analyzing the variance, that it was found that there are statistically indication differences between the study groups where the students of the Faculty of Engineering surpassed the students of the College of Science while the students of the College of Medicine occupied the last rank, in the end, the researcher attributes those results to the type of courses that they underwent during their university studies.